The Role of Metalanguage in an Explicit Literacy Instruction on Scientific Explanation - Tang, Kok-Sing; Rappa, N.A. (SPRINGER, 2020)
This paper illustrates the role of metalanguage in an explicit literacy instruction to talk about the forms and functions of scientific genres, particularly the genre of explanation. In the context of science, metalanguage refers to the technical terms for talking about scientific language using words like law, hypothesis, and evidence. Despite many efforts to use literacy strategies to address the challenges of learning scientific language, the conventional genres commonly found in science remain implicit in most science classroom teaching. In order to explicitly discuss the nature of scientific genres and how they are linked to scientific practices, scientific metalanguage provides a potential literacy tool. To illustrate this argument, we draw on a case study where four teachers and their grade 9 students learned how to use a specific type of metalanguage to describe scientific explanation. Analysis of their classroom discourse showed that the use of the metalanguage facilitated explicit communication about the logical sequence, epistemic structure, and validity of scientific explanation. Based on the findings, we discuss the usefulness of metalanguage for teachers and students to describe and analyze scientific genres as well as how these genres are used to construct and communicate scientific knowledge.